Integrating Genre Based Approach with Canva to Improve Twelfth Grade Students' Reading Comprehension - Fatma Septiari; Mutiara Ayu (LPPM Universitas PGRI Semarang, 2026)
This study investigates the effectiveness of the Genre-Based Approach (GBA) integrated with Canva in enhancing students’ reading comprehension. Despite the growing emphasis on reading skills in English language learning, many students still struggle to understand text structures, identify key ideas, and recognize specific vocabulary. This gap highlights the need for innovative approaches that combine structured pedagogy with digital media. The objective of this study was to determine whether the integration of GBA and Canva could significantly improve students’ reading comprehension. The research was conducted at SMA Negeri 8 Bandar Lampung with 28 second-grade students as participants. A pre-test and post-test design was employed, and the instrument used consisted of 40 validated multiple-choice items. Data analysis was carried out using SPSS with a paired sample t-test. The findings showed a substantial increase in the mean score, from 24.46 in the pre-test to 33.57 in the post-test, resulting in a mean difference of 9.11 points. The statistical test confirmed the significance of this improvement, with a p-value of .000 (< .05). These results demonstrate that the application of GBA supported by Canva effectively enhances reading comprehension skills. It can be concluded that structured genre-based instruction, when combined with engaging digital tools, provides a meaningful and effective learning experience in secondary education.